Pelatihan dan Implementasi Pelaporan Keuangan Zakat, Infak, dan Sedekah Berbasis Digital di Masjid Jami Al-Mujahidin Bintara Bekasi Barat - Pratiwi, Monica Weni; Lucyanda, Jurica; Iman Santoso, Berkah; Rudianto, Dudi; Annastasya Nurdini, Dinda; Karlina, Rina (LPkM Universitas Bakrie, 2022)
Mosque is an entity where some sources of funds come from the community or public in the form of waqf, grants, infaq and alms. Mosques are often in the public spotlight regarding the management of funds collected from the ummah and the community, so that high transparency and accountability are needed from the mosque administrators in financial reporting. Jami Al-Mujahidin Masjid Bintara, West Bekasi which is a large mosque and has been supervised by the ministry of religion. The limitations faced by the mosque manager is that it has not done financial reporting in accordance with accounting standards, so needs to be trained in preparing digital-based financial statements in accordance with the Statement of Financial Accounting Standards (PSAK) No. 109 on accounting for zakat, infaq and alms. This training aims to facilitated the management of Mosque to easily prepare the digital-based financial statement in accordance with accounting standards and can implement the transparency and accountability. The method of activity is carried out offline at the Jami Al-Mujahidin Mosque Hall which was attended by the administrators of the Jami Al-Mujahidin Masjid Bintara, West Bekasi. The training material provided consists of understanding, recognizing, and measuring zakat, infaq, and alms; accounting transactions of non-halal funds; zakat, infaq, and alms accounting financial statements; and the use of financial reporting applications based on PSAK No. 109 based on digital. After participating in this program, all mosque administrators or managements can understand the objectives and benefits of financial reporting and can implement the preparation of financial statements in accordance with applicable standards by using a digital-based financial statement. With the limited time for activities, monitoring and evaluation of the implementation of digital-based financial statement applications according to applicable standards will be carried out in subsequent activities.